Penguatan Pemahaman Mahasiswa Tingkat Akhir dalam Penulisan Karya Tulis Ilmiah Melalui Sosialisasi Buku Saku Penulisan Karya Tulis Ilmiah - Muthmainnah, Riyadatul; Laoli, Victorinus; Suwarno, Try Edi; Pulungan, Faisal Fadly; Prabowo, Kristianto Tricahya (Universitas Bangka Belitung, 2024)
This study aims to strengthen the understanding of final-year students in writing scientific papers through the dissemination of a scientific writing handbook. The approach methods used are comprehensive, participatory, and technology-based. This activity involved 60 students from the DIII Accounting Program, as well as course instructors and the program coordinator as facilitators. The dissemination was designed to provide an in-depth understanding of the structure, methods, and ethics of scientific writing, which is expected to enhance students' competence in completing their final projects. The results of the dissemination show a significant improvement in students' ability to understand and apply scientific writing concepts. Thus, this program is expected not only to equip students with the necessary writing skills but also to prepare them to face academic and professional challenges in the future. Keywords Scientific Writing, Dissemination, Final-Year Students